Crystal structures and Hirshfeld surface analysis of transition-metal complexes of 1,3-azolecarboxylic acids - Natthaya Meundaeng (2019)
The crystal structures of five new transition-metal complexes synthesized using thiazole-2-carboxylic acid (2-Htza), imidazole-2-carboxylic acid (2-H2ima) or 1,3-oxazole-4-carboxylic acid (4-Hoxa), namely diaquabis(thiazole-2-carboxylato-κ2N,O)cobalt(II), [Co(C4H2NO2S)2(H2O)2], 1, diaquabis(thiazole-2-carboxylato-κ2N,O)nickel(II), [Ni(C4H2NO2S)2(H2O)2], 2, diaquabis(thiazole-2-carboxylato-κ2N,O)cadmium(II), [Cd(C4H2NO2S)2(H2O)2], 3, diaquabis(1H-imidazole-2-carboxylato-κ2N3,O)cobalt(II), [Co(C4H2N2O2)2(H2O)2], 4, and diaquabis(1,3-oxazole-4-carboxylato-κ2N,O4)cobalt(II), [Co(C4H2NO3)2(H2O)2], 5, are reported. The influence of the nature of the heteroatom and the position of the carboxyl group in relation to the heteroatom on the self-assembly process are discussed based upon Hirshfeld surface analysis and used to explain the observed differences in the single-crystal structures and the supramolecular frameworks and topologies of complexes 1-5.